Application of the Certainty Factor Method for Diagnosing Mental Illness Disease - Mirah, Alta; Maulita, Yani; Simanjuntak, Magdalena (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Mental illness is a disease that is widespread among Indonesian people. Mental illness, also known as mental health disorder, is a term that refers to various conditions that can affect a person's thoughts, moods, feelings or behavior. However, there are still many Indonesian people who do not recognize and indicate the existence of mental illness because many people do not pay attention to their mental health or those around them. the small number of psychiatrists available in each area and the costs required are also not small, causing ordinary people to be reluctant to carry out examinations with psychiatrists, this of course leads to delays in treatment which can even be fatal. To prevent the increase in sufferers of mental illness, a system is needed that can store the knowledge of experts or psychologists who understand how to handle mental illness. An expert expert system is an artificial intelligence program that combines a knowledge base with an inference system to emulate an expert. The certainty factor method is a method used to solve cases of uncertainty, where the size is based on a fact or rule that can be used in expert systems. With the existence of an expert system for diagnosing mental illness, the general public can recognize early symptoms of mental illness, so treatment can be done earlier. From the results of the trials conducted, the results of the mental illness expert system were obtained with the highest score, namely depression with a confidence value of 90.02%.